Tandem Electrocatalytic Nitrate Reduction to Ammonia on MBenes - Zhang, Guike; Li, Xiaotian; Chen, Kai; Guo, Yali; Ma, Dongwei; Chu, Ke (Angewandte Chemie International Edition, 2023)
We demonstrate the great feasibility of MBenes as a new class of tandem catalysts for electrocatalytic nitrate reduction to ammonia (NO3RR). As a proof of concept, FeB2 is first employed as a model MBene catalyst for the NO3RR, showing a maximum NH3‐Faradaic efficiency of 96.8 % with a corresponding NH3 yield of 25.5 mg h−1 cm−2 at −0.6 V vs. RHE. Mechanistic studies reveal that the exceptional NO3RR activity of FeB2 arises from the tandem catalysis mechanism, that is, B sites activate NO3− to form intermediates, while Fe sites dissociate H2O and increase *H supply on B sites to promote the intermediate hydrogenation and enhance the NO3−‐to‐NH3 conversion. MBenes are demonstrated to be a new class of tandem catalysts for electrocatalytic nitrate reduction to ammonia (NO3RR). Taking FeB2 as the proof‐of‐concept paradigm, mechanistic studies unveil that the synergistic tandem effect of Fe and B atoms promotes NO3− activation and intermediate hydrogenation to enhance the NO3RR activity and selectivity.